Evidence-to-practice gaps in the management of community-dwelling Australian patients with ischaemic heart disease - Schmid, O.; Stafford, Leanne; Bereznicki, L. (Wiley-Blackwell Publishing Ltd., 2015)
© 2015 John Wiley & Sons Ltd.Summary What is known and objective Ischaemic heart disease (IHD) is a major cause of death in developed countries. Patients with IHD are at greater risk of subsequent myocardial infarction (MI). International studies suggest that guideline recommended therapies proven to reduce this risk are underutilised. The objectives of this study were to review the use of guideline-recommended medications for the secondary prevention of IHD in Australians and identify patient characteristics influencing use of these medications. Methods The medication regimens of community dwelling Australians with documented IHD who received a Home Medicines Review (HMR) between January 2010 and September 2012 were extracted from a pharmacist decision support software database and retrospectively reviewed. Each patient's use of antithrombotics; angiotensin converting enzyme inhibitors (ACEIs) or angiotensin receptor blockers (ARBs); statins; and ß-blockers (BBs) or non-dihydropyridine calcium channel blockers (CCBs) was evaluated in conjunction with documented contraindications. Guideline concordance in all four categories was classified as 'Optimal Medical Therapy' (OMT). Univariate and multivariate analyses identified patient characteristics influencing OMT use. Results and discussion Of the 5396 patient medication regimens reviewed, 24·3% demonstrated OMT. Guideline concordance was observed in 91·6%, 75·6%, 74·8%, and 42·4% of patients for antithrombotics, statins, ACEI/ARBs, and BB/CCBs, respectively. The independent predictors of not receiving OMT were age 75 years or over (adjusted odds ratio [AOR] 0·76; 95% confidence interval [CI] 0·67-0·87), asthma (AOR 0·69; 95% CI 0·57-0·84), and depression or anxiety (AOR 0·84; 95% CI 0·71-0·99). Diabetes (AOR 1·20; 95% CI 1·04-1·38), hypertension (AOR 1·56; 95% CI 1·36-1·79) and a high Charlson Comorbidity Index score (AOR 1·37; 95% CI 1·15-1·64) independently predicted receipt of OMT. What is new and conclusion Only one quarter of community dwelling Australian patients with IHD receive antithrombotics, ACEI/ARBs, BB/CCBs and statins. The potential consequences of these evidence-to-practice gaps are exacerbated by Australia's increasing prevalence of IHD. Healthcare professionals must work to ensure that recommended therapies are prescribed and adhered to long-term, especially in the elderly and patients with asthma and mental health problems, to reduce IHD-related mortality and morbidity and the consequent healthcare and financial impact. Only one quarter of community dwelling Australian patients with IHD receive antithrombotics, ACEI/ARBs, BB/CCBs and statins. The potential consequences of these evidence-to-practice gaps are exacerbated by Australia's increasing prevalence of IHD. All healthcare professionals involved in the care of patients with IHD need to focus on ensuring that these agents are appropriately prescribed and patients are supported in adhering to them long-term.